The Influence of the Principal's Situational Leadership, Organizational Culture and Teacher Performance on the Effectiveness of Cooperation between the Business World and the Industrial World at SMKN throughout Mataram City - Budi Santoso; Muhammad Thohri; Yudin Citriadin (al-Afkar, Journal For Islamic Studies, 2024)
This research aims to determine the influence of the Principal's Situational Leadership, Organizational Culture and Teacher Performance on the Effectiveness of Cooperation between the Business World and the Industrial World at SMKN throughout Mataram City. This research consists of three variables, namely the Principal's Situational Leadership (X_1), Organizational Culture (X_2), and Teacher Work (X_3) as independent variables Effectiveness of Cooperation between the Business World and the Industrial World is bound (Y). This research uses a quantitative approach. The population in this study was 245 teachers. Sampling technique using random sampling. Data collection using instruments that have been tested for validity and reliability. The data that has been collected is then tested using prerequisite tests, namely normality, linearity and multicolonierity. The hypothesis tests used in this research are the F test and the T test which were analyzed using SPSS 25.0. The results of this research show that: (1) partially the principal's situational leadership (X_1) influences the effectiveness of cooperation between the business world and the industrial world (Y) as evidenced by the value of multiple linear regression analysis that the sig value is 0.003 (003<0.05), (2) Organizational Culture (X_2) influences the effectiveness of cooperation between the business world and the industrial world (Y), it is proven by the value of multiple linear regression analysis that the sig value. value 0.006 (006<0.05) teacher performance (X_3) has no effect on the effectiveness of cooperation between the business world and the industrial world (Y), proven by the value of multiple linear regression analysis that the sig value. value 0.506 (006>0.05). Meanwhile, simultaneously the principal's situational leadership (X_1), organizational culture (X_2), teacher performance (X_3) have an influence on the effectiveness of cooperation between the business world and the industrial world.